2019
DOI: 10.47176/mjiri.33.50
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different techniques of AFO construction for hemiplegia patients: A systematic review

Abstract: Ankle foot orthosis (AFO) is frequently used to improve gait deviations in patients with hemiplegia. AFOs prevent foot drop in the swing phase and promote heel strike in the early stance phase of gait. →What this article adds: A variety of studies have reported the AFO is an effective tool for improving the gait pattern of hemiplegia patients. This study provided some guidelines to robustly report AFO interventions, mechanical characteristic of AFOs, and efficacy of AFOs' construction techniques, testing strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
(102 reference statements)
0
11
0
Order By: Relevance
“…In this study, while using spring damper AFO, the twopeak pattern of vGRF was near the normal condition. However, some studies have indicated that PLS or some conventional articulation AFOs with plantarflexion resistance were unable in restoring the normal pattern of vGRF [4]. In these AFOs, the peaks of vGRF at the early and terminal stance were decreased, and an extra peak was observed during the midstance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, while using spring damper AFO, the twopeak pattern of vGRF was near the normal condition. However, some studies have indicated that PLS or some conventional articulation AFOs with plantarflexion resistance were unable in restoring the normal pattern of vGRF [4]. In these AFOs, the peaks of vGRF at the early and terminal stance were decreased, and an extra peak was observed during the midstance.…”
Section: Discussionmentioning
confidence: 99%
“…The vGRF pattern could be explained by considering the magnitude of the acceleration and applied force, arising from the weight of the body in the opposite direction of the ground force (Newton's second law) [19]. Based on this concept, different types of lower or assistive devices may produce different vGRF patterns [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations